Innovation outcomes and processes in infrastructure projects – a comparative study of Design-Build and Design-Build-Maintenance contracts. Issue 2 (1st February 2022) - Larsson, Johan; Eriksson, Per Erik; Lingegård, Sofia; Järvenpää, Anna-Therése
Abstract: Innovation is often seen as essential for long-term development in the construction industry, but its actual outcomes and processes in construction projects require more attention. Many studies on procurement strategies and delivery systems have focussed on the public transport infrastructure sector, whereas most construction innovation scholars have addressed the innovation phenomenon in construction generally. Thus, the purpose of this study is to compare how two delivery systems, design-build (DB) and design-build-maintenance (DBM), influence project-level innovation. Findings are based on empirical data from a multiple case study of six infrastructure projects, three with DB contracts and three with DBM contracts, in which 12 innovations are identified, described, and compared. The findings show that various kinds of innovations in terms of outcomes and processes are implemented in infrastructure projects, and that the delivery system do effect both dimensions. Long maintenance responsibilities tend to spur contractors to engage in early exploration of sustainable solutions that could be of long-term benefit. The research contributes to procurement literature by exemplifying how delivery systems influence both the outcomes and processes of project-level innovations. It also increases our knowledge about construction innovation as a multi-dimensional phenomenon.